2006
DOI: 10.1002/ajp.20240
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of rhesus macaques (Macaca mulatta) in Nepal

Abstract: Indian-origin rhesus macaques (Macaca mulatta) have long served as an animal model for the study of human disease and behavior. Given the current shortage of Indian-origin rhesus, many researchers have turned to rhesus macaques from China as a substitute. However, a number of studies have identified marked genetic differences between the Chinese and Indian animals. We investigated the genetic characteristics of a third rhesus population, the rhesus macaques of Nepal. Twenty-one rhesus macaques at the Swoyambhu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…As for the Chinese and Burmese rhesus macaques, the Indian and Nepalese rhesus macaques form a unique clade, suggesting that genetic exchange occurs between these populations. Kyes et al (2006) also showed a close relationship between the Nepalese and Indian populations but noted that Nepalese animals were highly homogeneous as observed in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…As for the Chinese and Burmese rhesus macaques, the Indian and Nepalese rhesus macaques form a unique clade, suggesting that genetic exchange occurs between these populations. Kyes et al (2006) also showed a close relationship between the Nepalese and Indian populations but noted that Nepalese animals were highly homogeneous as observed in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Among the 37 alleles, 27 had been documented before and could be found in GenBank; the other 10 alleles were not documented before and, to our knowledge, should be novel MhcMamu-DQB1 sequences. Geographic differences are common phenomena as far as the polymorphism of MHC genes is concerned [26]. When alignment was performed with nucleotide sequences retrieved from GenBank, 10 novel sequences were identified in Chinese rhesus macaques, which tend to cluster with sequences common to the earlier and current studies on the phylogenetic tree.…”
Section: Discussionmentioning
confidence: 99%
“…In fact data have accumulated in recent years showing significant differences in MHC genes between these two populations [16,19,26,30 -32]. For example, the MhcMamu-A1*01 allele has been detected in 14 -46% of Indian-origin rhesus macaques but has been shown to be rare in Chinese rhesus macaques [26,30,33,34]. Despite extensive progresses, knowledge about the MHC genotype of Chinese rhesus macaques is still too limited to fulfill its role in biomedical research corresponding to that usually played by Indian macaques in the past.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chinese rhesus macaques have been increasingly used as a substitute for Indian rhesus macaques in the research of AIDS and other human diseases (11). However, several researches of Chinese rhesus macaques focused on the morphometrics (3) and genetic background (4) differences comparing with their Indian counterparts.…”
Section: Discussionmentioning
confidence: 99%